1994
DOI: 10.1042/cs0860091
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Homoeostasis in man: Influence of Protein Intake on the Amplitude of Diurnal Cycling of Body Nitrogen

Abstract: 1. The diurnal nature of nitrogen (N) homoeostasis was investigated in adults fed increasing protein intakes. N balance was estimated during a 48 h period of consecutive 12 h periods of feeding hourly meals and fasting, after 12 days of adaptation to diets containing 0.36 +/- 0.01, 0.77 +/- 0.03, 1.59 +/- 0.08 and 2.31 +/- 0.65 g of protein day-1 kg-1. N losses were determined from measured urinary N excretion corrected for changes in the body urea pool, and estimated faecal and miscellaneous losses. [13C]Leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
80
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 0 publications
9
80
0
Order By: Relevance
“…The rates of leucine oxidation determined by Price et al (1994) in the fed and fasting states show a similar pattern to the N excretion shown in Figure 4. However, when leucine oxidation rates were converted to equivalent rates of N excretion, by the same method as that employed by El Khoury et al (1994), described in the previous Section, the values are in all cases lower than expected; between 61% Figure 3 Simulated curves for leucine oxidation and net urea production rates, illustrating damping of the apparent rate of urea production by the body urea pool.…”
Section: Protein Turnover In Relation To Dietary Protein Levelsupporting
confidence: 58%
See 4 more Smart Citations
“…The rates of leucine oxidation determined by Price et al (1994) in the fed and fasting states show a similar pattern to the N excretion shown in Figure 4. However, when leucine oxidation rates were converted to equivalent rates of N excretion, by the same method as that employed by El Khoury et al (1994), described in the previous Section, the values are in all cases lower than expected; between 61% Figure 3 Simulated curves for leucine oxidation and net urea production rates, illustrating damping of the apparent rate of urea production by the body urea pool.…”
Section: Protein Turnover In Relation To Dietary Protein Levelsupporting
confidence: 58%
“…More recently, there has been a variety of studies of whole-body protein turnover at low to moderate levels of protein intake in humans (Robinson et al, 1990;Garlick et al, 1991;Campbell et al, 1995;Pannemans et al, 1995;Gibson et al, 1996) and also at high intake (Yang et al, 1986;Fern et al, 1991). However, a recent and systematic series of studies with levels of protein intake extending from low to high (0.36 ± 2.31 gakgad) has further developed the concepts of immediate effects of food intake and adaptive responses Price et al, 1994;Quevedo et al, 1994). As in earlier studies described above (Motil et al, 1981;Clugston & Garlick, 1982;Melville et al, 1989), the experimental protocol consisted of a day divided into two notional periods, 12 h of fasting (overnight) and 12 h of feeding, involving hourly small meals.…”
Section: Protein Turnover In Relation To Dietary Protein Levelmentioning
confidence: 99%
See 3 more Smart Citations